The Difficulty of Being Good: On the Subtle Art of Dharma - Mehta, Reena Apurva (Prabandhan: Indian Journal of Management, 2015)
The book review analyzed Gurcharan Das’s book The Difficulty of Being Good: On the Subtle Art of Dharma. This book operates from the perspective of the epic The Mahabharata. The author has attempted to explain the meaning of Dharma by dissecting the behavioural patterns of the characters in The Mahabharata. The book discusses how the battle of Kurukshetra and the characters of The Mahabharata are the paradigms of different crises and moral dilemmas faced by human nature and different cultures.